Superficial Siderosis and Microbleed Restricted in Cortex Might Be Correlated to Atrophy and Cognitive Decline in Sneddon's Syndrome - Yao, Ming; Zhao, Jiuliang; Jiang, Nan; Li, Libo; Ni, Jun (Frontiers in Neurology, 2020)
Objective: Sneddon’s syndrome is a rare non-inflammatory arteriopathy affecting small and medium-sized arteries, characterized by a generalized livedo reticularis and recurrent transient ischemic attack or ischemic stroke. Hemorrhagic stroke was reported in limited cases, but microbleeds and superficial siderosis were rarely issued. We aimed to investigate the hemorrhagic imaging features of Sneddon’s syndrome and explore the possible mechanism and clinical relevance. Methods: Clinical data and cerebral MR imaging including T2* sequence of 7 consecutive patients with Sneddon’s syndrome were reviewed. Results: The most common neurological manifestations were cognitive impairment and stroke attack(71.4%), followed by seizures and movement disorder(28.6%). Cerebral microbleeds were detected in six patients on T2* sequence，all of them presented with cortical microbleeds, only one of them with microbleeds in basal ganglion. More than 5 microbleeds were observed in four of these six patients. The majority of the microbleeds were predominantly cortical restricted and especially located in the cortical watersheds. Multiple superficial siderosis were identified mainly involving cortical watersheds in five cases. Significant cerebral atrophy with prominent secondary white matter hyperintensities in bilateral cortical watersheds were also observed. Abnormal tortuous and multiple focal occlusion of bilateral distal MCA were shown in one patient by DSA. No stenosis of proximal segment of cerebral arteries was detected in all the patients. Conclusions: This is the first report illustrating abundant cortical microbleeds and superficial siderosis mainly involved the anterior and posterior cortical watersheds in Sneddon’s syndrome. The surprisingly identical topographic distribution of hemorrhagic lesions and the obvious atrophy suggest cerebral atrophy might be secondary to the microangiopathy related hemorrhagic lesions and further contribute to the neurological deficit, especially the early cognitive decline in Sneddon syndrome.